Do state minimum markup/price laws work? Evidence from retail scanner data and TUS-CPS. (3rd October 2016) - Huang, Jidong; Chriqui, Jamie F; DeLong, Hillary; Mirza, Maryam; Diaz, Megan C; Chaloupka, Frank J
Abstract : Background: Minimum markup/price laws (MPLs) have been proposed as an alternative non-tax pricing strategy to reduce tobacco use and access. However, the empirical evidence on the effectiveness of MPLs in increasing cigarette prices is very limited. This study aims to fill this critical gap by examining the association between MPLs and cigarette prices. Methods: State MPLs were compiled from primary legal research databases and were linked to cigarette prices constructed from the Nielsen retail scanner data and the self-reported cigarette prices from the Tobacco Use Supplement to the Current Population Survey. Multivariate regression analyses were conducted to examine the association between MPLs and the major components of MPLs and cigarette prices. Results: The presence of MPLs was associated with higher cigarette prices. In addition, cigarette prices were higher, above and beyond the higher prices resulting from MPLs, in states that prohibit below-cost combination sales; do not allow any distributing party to use trade discounts to reduce the base cost of cigarettes; prohibit distributing parties from meeting the price of a competitor, and prohibit distributing below-cost coupons to the consumer. Moreover, states that had total markup rates >24% were associated with significantly higher cigarette prices. Conclusions: MPLs are an effective way to increase cigarette prices. The impact of MPLs can be further strengthened by imposing greater markup rates and by prohibiting coupon distribution, competitor price matching, and use of below-cost combination sales and trade discounts.